Helicobacter pylori Infection as a Risk Factor for Hepatocellular Carcinoma: A Case-Control Study in Ethiopia - Hailemichael Desalegn Mekonnen; Henok Fisseha; Tewodros Getinet; Fisseha Tekle; Peter R. Galle (International Journal of Hepatology)
Background and Aims. Hepatocellular carcinoma is a major cause of cancer death worldwide, accounting for over half a million deaths per year. Its incidence varies with geographic locations and the type of etiologic factors. In Ethiopia, unidentified causes of liver disease are of sizeable proportion. Recent studies have shown an association of H. pylori infection with different spectrums of chronic liver disease. This study was conducted at St. Paul’s Hospital Millennium Medical College in Ethiopia and assesses liver cancer and the association with H. pylori infection. Method. A prospective case-control study conducted on patients with chronic liver disease presenting with a suspicious liver lesion and diagnosed to have HCC in the Gastrointestinal (GI) Clinic of St. Paul’s Hospital MMC from Dec 30, 2016, to Nov 1, 2017 G.C. Descriptive surveys on clinical history and physical examination and laboratory profiles were obtained, and the clinical course of the patients including the type of treatment was followed prospectively. Control cases were taken from adult patients without evidence of liver disease in the internal medicine clinic coming for routine evaluation. After collection data were analyzed using SPSS version 23 and associations were assessed using chi-square test. Binary logistic regression was used to assess the association of HCC with different variables and H. pylori infection. All variables with p-value <0.05 were considered as statistically significant. Results. One hundred twenty patients were analyzed with equal representation of cases and controls. The majority of patients with HCC were male with a mean age of 36 years. Older age adjusted Odds Ratio (AOR) (95%CI, p-value) 1.07(1.03-1.09, <0.001), viral hepatitis B (AOR) (95%CI, p-value) 6.19 (1.92-19.93, 0.002), and H. pylori infection (AOR) (95%CI, p-value) 5.22 (2.04–13.31, <0.001) were statistically significantly associated with HCC. Conclusion. H. pylori infection is associated with HCC in this case-control study. This study supports the emerging evidence of H. pylori association with other extra-gastric manifestations.